WE WANT TO CONTRIBUTE TOO: The narrative experience of immigrants with career qualifications and their acceptance into the Icelandic labor market - Renner, Margo, 1953- (2010)
The purpose of this study is to shed light on the experiences of professionally educated individuals who have immigrated to Iceland and their subsequent accounts of obtaining recognition and validation for their educational degrees and career experience. Qualitative methods were used to acquire an understanding of the typical obstacles that immigrants holding professional degrees have encountered and the effects that these obstacles have had on their adjustment to living in Iceland. Data was acquired through personal interviews with seven individuals from ages 32-53. The results show that the career paths of professionals attempting to use their qualifications in Iceland can be rough and stony. On the other hand, the results of this research also showed that flexibility can lead to other career paths that are equally fortuitous and that it is impossible to emphasize enough, the importance of being open-minded when searching for career opportunities. Lastly the research affirms the value of career and educational counseling for newly arrived immigrants to Iceland. Counseling can aid in understanding the struggle and frustration of culture shock. It also emphasizes the usefulness of language learning. It underscores the importance in helping to guide immigrants through the process of validation of credentials and aid in a job search that will assist the individual either to continue his present career or start a new and valuable path. Whatever option is chosen, the availability of validation of education and experience in addition to the realization of choices, can benefit both the immigrant and Iceland. ÚTDRÁTTUR Tilgangur þessarar rannsóknar er að varpa ljósi á reynslur faglærðra innflytjenda á Íslandi við að fá námsgráður og starfsreynslur sínar metnar og viðurkenndar. Sjö þátttakendur voru valdir til að öðlast skilning á hindrunum sem innflytjendur hafa staðið frammi fyrir. Gögnum var safnað í gegnum einkaviðtöl við einstaklinga á aldrinum 32-53 ára. Niðurstöður rannsóknarinnar sýna að tilraunir faglærðra ...